A predictive model of risk and outcomes in tissue expander reconstruction: A multivariate analysis of 9786 patients. Issue 6 (December 2013) - Hanwright, Philip J.; Davila, Armando A.; Mioton, Lauren M.; Fine, Neil A.; Bilimoria, Karl Y.; Kim, John Y. S.
Abstract Outcomes of tissue expander breast reconstruction show variability based on presurgical risk factors. Few comprehensive, multi-institutional risk analyses exist. Patients who underwent tissue expander reconstruction were identified in a multi-institutional registry that spans over 240 institutions with over 200 variables per patient. Bivariate analysis of preoperative variables was performed across outcomes. Multivariate logistic regression was used to adjust for confounders and identify risk factors for complications. In 9786 total tissue expander patients, 526 (5.38%) patients experienced one or more complications. Wound infection and reoperations occurred in 3.45% and 6.76% of patients, respectively. Body mass index (BMI) was found to be a significant independent risk factor for overall morbidity, reoperation, prosthesis failure, and wound infection. Overweight, obese, and morbidly obese patients were at 1.7-, 2.6-, and 5.1-times greater risk of morbidity, respectively (p < 0.001 for all). Reconstructive timing, combined surgical procedures, and neoadjuvant chemotherapy were not found to be significant predictors of morbidity. The odds of developing complications were 1.5- and 1.3-times greater in smokers and patients over the age of 50, respectively (p = 0.001 and p = 0.015). For each additional hour of surgery, the odds of morbidity increased 1.26-times (p < 0.001). Precise risk profiles garnered from multi-institutional studies can help improve patient selection and education. Overall, tissue expander reconstruction was found to be safe, with relatively few complications. Operative time, BMI, and smoking were consistently found to be independent risk factors for postoperative morbidity.